School dropout in the courses of Technical Professional Education of Medium Level in the distance modality: a study in a Federal Public Institution of Minas Gerais (Research, Society and Development, 2020)
Nowadays, dropout represents one of the great challenges faced by school institutions in the various teaching modalities, especially in Distance Education (DE). Despite the growing number of institutions that offer some type of distance learning course and the significant number of enrolled students, it is clear that dropout is recurring. In this understanding, the objective of this research was to identify the dropout rates and investigate the main causes of the non-permanence of the students of the Technical Vocational Education courses in the Distance Education (EPTNMEaD) offered in a Federal Public Institution of Minas Gerais. To obtain the information, bibliographic, documentary and survey procedures were applied based on the application of online questionnaires to dropout students. It was found that in the third module of the courses (penultimate module) the dropout rate was 50%. Considering that non-permanence is determined by factors both internal and external to the institution, we sought to investigate these factors separately. Among the internal factors that contributed to the non-permanence, the lack of planning of the subjects, low attractiveness or stimulus of the course and low interactivity of the Virtual Theaching and Learning Environment (AVEA) stand out. Regarding external factors, the difficulty in organizing and managing time was the factor that stood out. Therefore, the knowledge of the reasons that cause the non-permanence is of fundamental importance for the debate of possible solutions to the problem and the elaboration of action strategies.